Theology and identity : the impact of culture upon Christian thought in the second century and in modern Africa. - Bediako, Kwame (Regnum studies in mission., 1999)
Kwame Bediako examines the question of Christian identity in the context of the Greco-Roman culture of the early Roman Empire. He then addresses the modern African predicament of quests for identity and integration.